2007
DOI: 10.1590/s0103-50532007000500019
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase extraction of nitro-PAH from aquatic samples and its separation by reverse-phase capillary liquid chromatography

Abstract: Neste trabalho é proposta uma metodologia analítica para extrair 1-nitronaftaleno, 2-nitrofluoreno, 9-nitroantraceno, 3-nitrofluoranteno e 1-nitropireno como compostos modelos para nitropoliaromáticos (nitro-HPA) em amostras aquáticas. A cromatografia líquida capilar com detecção UV on-column (μLC-UV) foi empregada para separar e quantificar todos os cinco nitro-HPA extraídos. Duas técnicas diferentes de extração foram testadas e comparadas: extração líquido-líquido (LLE) e extração em fase sólida (SPE) com do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Other studies of wastewaters have used Solid Phase Microextraction (SPME) 9 or Solid Phase Extraction (SPE) [10][11][12]. Direct mode SPME is not feasible, due to attack on comercially used fibres by compounds present in produced water.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of wastewaters have used Solid Phase Microextraction (SPME) 9 or Solid Phase Extraction (SPE) [10][11][12]. Direct mode SPME is not feasible, due to attack on comercially used fibres by compounds present in produced water.…”
Section: Introductionmentioning
confidence: 99%
“…SPE, LLE, and SPME have been used to extract NPAHs from water samples . Compared to other methods, SPME is easier to operate, more economical, and more efficient for the extraction of NPAHs .…”
Section: Introductionmentioning
confidence: 99%
“…NPAHs were first found in the Suimon river water in the 1980s [15], after which most studies were focused on NPAHs in sediments [15][16][17] making studies in water relatively rare. SPE, LLE, and SPME have been used to extract NPAHs from water samples [18][19][20]. Compared to other methods, SPME is easier to operate, more economical, and more efficient for the extraction of NPAHs [20].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are a common part of the air where they are mostly adsorbed on the solid atmospheric particles (dust fractions). NPAHs are identified as a class of genotoxic environmental pollutants (Netto et al 2000;Lopes et al 2005) and the Ames Salmonella test has shown that NPAHs generally are more mutagenic than their parent PAHs (Barek et al 1996;Lopes and deAndrade 1996;Toledo, Lanças, and Carrilho 2007). The position of the nitro group on the aromatic rings significantly affects the metabolism, mutagenicity, and carcinogenicity of these compounds.…”
Section: Introductionmentioning
confidence: 99%